Measuring spatial price differentials at the basic heading level: a comparison of stochastic index number methods - Sebastian Weinand (AStA Advances in Statistical Analysis, 2021)
Spatial price comparisons rely to a high degree on the quality of the underlying price data that are collected within or across countries. Below the basic heading level, these price data often exhibit large gaps. Therefore, stochastic index number methods like the Country–Product–Dummy (CPD) method and the Gini–Eltetö–Köves–Szulc (GEKS) method are utilised for the aggregation of the price data into higher-level indices. Although the two index number methods produce differing price level estimates when prices are missing, the present paper demonstrates that both can be derived from exactly the same stochastic model. For a specific case of missing prices, it is shown that the formula underlying these price level estimates differs between the two methods only in weighting. The impact of missing prices on the efficiency of the price level estimates is analysed in two simulation studies. It can be shown that the CPD method slightly outperforms the GEKS method. Using micro data of Germany's Consumer Price Index, it can be observed that more narrowly defined products improve estimation efficiency.
Keywords: 510; Spatial price comparison; Below basic heading; Multilateral index number methods; CPD method; GEKS method